Mechano-acoustic feedback in the case of an interaction between a sound source and a resonance system - M. MEISSNER (Archives of Acoustics)
This paper presents an analysis of the mechano-acoustic feedback between a sound source and a resonance system. In the theoretical part, the change in the mechanical impedance of the sound source which occurs when the source is affected by the external acoustic field is determined; and subsequently, using the image source method, the distribution of the standing pressure wave between the source and the resonator is given. The combination of the relations thus derived permits the distribution of the standing pressure wave between the source and the resonator to be determined, with consideration given to changes in the radiation impedance of the source and the mechanical parameters of the resonator. The experimental part gives the results of measurements of the dependence of the mean value of the modulus of the pressure amplitude of the standing wave on frequency for different resonance frequencies of the resonator and a comparison of the experimental and theoretically determined results in the case of an interaction between a sound source and a rigid baffle.